The Rise of Neo Banking in India: Decoding Growth Drivers - Dr. T N Anuradha (International Journal of New Media Studies: International Peer Reviewed Scholarly Indexed Journal, 2023)
The extensive changes in Indian Banking from the traditional banking to digital banking, today are in technologically driven banking or Financial Technology (Fintech) field with and the Internet of things (IOT) and Artificial Intelligence (AI). The study examines how Fin Tech has revolutionized the traditional banking in India, with special reference to the growth and opportunities in Neo banking during COVID -19. Neo banks are digital-only banks are with no physical branches, cash free accounts; cost reduction as they don’t have any physical presence. And they are most preferred form among the millennials. Neo banks are providing personalised value-added services to the tech savvy millennials.